Nabi dan Mukjizat - Antonius Hari Kustono (Jurnal Orientasi Baru, 2013)
Three key terms are used of the prophet: roeh, hozeh, nabi. The terms roeh and hozeh are translated as seer, while the most important term is nabi, which is usually translated prophet. It means one who is called to speak. There is no particular reference to the prophets as men of miracle in the Old Testament. However, we have two prophets, Elijah and Elisha, who performed amazing and powerful miracles of the Lord. Within about sixtyfive years after Solomons death the nation of Israel had reverted back to such a state of apostasy from God that the prophet Elijah was raised up to witness against them. He was succeeded by Elisha who asked for a double portion of Elijahs miraculous powers (2 Kings 2:9). Both men prophesied in one of Israels greatest times of disloyalty to God. Through their stories and miracles we are reminded to the Hebrew word dabar which is sometimes used in reference to the Divine Word and also in an active sense as the Divine Work.